Higher calcineurin inhibitor levels predict better kidney graft survival in patients with de novo donor‐specific anti‐HLA antibodies: a cohort study. (5th March 2017) - Béland, Marc‐Antoine; Lapointe, Isabelle; Noël, Réal; Côté, Isabelle; Wagner, Eric; Riopel, Julie; Latulippe, Eva; Désy, Olivier; Béland, Stéphanie; Magee, Ciara N.; Houde, Isabelle; De Serres, Sacha A.
Summary: The development of de novo anti‐HLA donor‐specific antibodies (dnDSA) is associated with poorer outcomes in kidney transplant recipients. Despite this, antibody screening post‐transplant is not widespread, largely because the optimal management of patients with dnDSA remains undetermined. We hypothesized that in this population, calcineurin inhibitor blood levels would be an independent predictor of graft loss. We analyzed a cohort of unsensitized patients for whom anti‐HLA antibody screening was performed prospectively post‐transplant. During the screening period between January 2005 and April 2016, 42 patients developed dnDSA. There was no difference in the clinical characteristics or the histological scores of patients biopsied for clinical indication versus those biopsied solely due to detection of dnDSA. Cox modeling revealed a strong relationship between mean tacrolimus levels following dnDSA detection and graft loss, with a hazard ratio of 0.49 (95% CI, 0.33–0.75), which persisted following adjustment for established independent predictors (HR, 0.52, 95% CI, 0.30–0.89). Kaplan–Meier analysis by tertiles of tacrolimus levels and receiver operating curve analysis concurred to show that a threshold of 5.3 ng/ml could be predictive of graft loss. These data suggest that anti‐HLA antibody monitoring post‐transplant could guide maintenance immunosuppression and improve graft outcomes.